Neuregulin-1 Accelerates Functional Motor Recovery by Improving Motoneuron Survival After Brachial Plexus Root Avulsion in Mice. (15th April 2019) - Chen, Shuangxi; Hou, Yuhui; Zhao, Zhikai; Luo, Yunhao; Lv, Shiqin; Wang, Qianghua; Li, Jing; He, Liumin; Zhou, Libing; Wu, Wutian
Abstract: Brachial plexus root avulsion (BPRA) results in the complete loss of motor function in the upper limb, mainly due to the death of spinal motoneurons (MNs). The survival of spinal MNs is the key to the recovery of motor function. Neuregulin-1 (Nrg1) plays fundamental roles in nervous system development and nerve repair. However, its functional role in BPRA remains unclear. On the basis of our findings that Nrg1 is down-regulated in the ventral horn in a mouse model of BPRA, Nrg1 may be associated with BPRA. Here, we investigated whether recombinant Nrg1β (rNrg1β) can enhance the survival of spinal MNs and improve functional recovery in mice following BPRA. In vitro studies on primary cultured mouse MNs showed that rNrg1β increased the survival rate in a dose-dependent manner, reaching a peak at 5 nM, which increased the survival rate and enhanced the pERK levels in MNs under H2 O2 -induced oxidative stress. In vivo studies revealed that rNrg1β improved the functional recovery of elbow flexion, promoted the survival of MNs, enhanced the re-innervation of biceps brachii, and decreased the muscle atrophy. These results suggest that Nrg1 may provide a potential therapeutic strategy for root avulsion. Highlights: RNrg1β increased the survival rate and enhanced the pERK levels in MNs under oxidative stress. RNrg1β improved the functional recovery of elbow flexion. RNrg1β promoted the survival of MNs, enhanced the re-innervation of biceps brachii, and decreased the muscle atrophy.